Strategic Flexibility: A Management Guide for Changing TimesStrategic Flexibility: A Management Guide for Changing Times, by HarriganKathryn Rudie. Lexington, MA: D. C. Heath and Company, 1985, 208 pp., $16.95, cloth. - Pearce, John A.; Winfrey, Frank L. (Academy of Management Review, 1986)
The article reviews the book ?Strategic Flexibility: A Management Guide for Changing Times,? by Kathryn Rudie Harrigan.